Analisis Bibliometrik : Fokus Penelitian Geometri Pada Pembelajaran Matematika di Indonesia (2017 -2023) - Iffah, Rona Dhiya Layli; Ningrum , Sri Adiningsih Utami; Sujadi , Imam (Program Studi Pendidikan Matematika, Universitas Nusantara PGRI Kediri, 2024)
Geometry is one of the contents that students must master during the math learning process, so research on this topic is widely done. This study aims to determine the trend of geometry research research themes that can be used as research topics in the future. This study uses bibliometric analysis, which uses a maximum limit of 200 articles throughout 2017-2023, google scholar is used to search data with geometry keywords through Harzing's Publish or Perish program, then narrowed down to get 171 articles. The results of this study indicate that the trend of publications with geometry research themes has increased in 2018 - 2019. While the theme of geometry research topics that have the opportunity to be used as research in the future there are two keywords namely LKPD and exploration.